MINERAL COLLECTIONS OF RUSSIA, PART II-TWELVE MUSEUM COLLECTIONS - Crook R.B. (My University, 2002)
Reviews the book 'Mineral Collections of Russia, Part II—Twelve Museum Collections,' edited by Dmitrii V. Rundqvist.
Keywords: MINERAL COLLECTIONS OF RUSSIA (BOOK)